The difference between multiculturalism and perspectivism - Chaparro Amaya, Adolfo (Estudios de Filosofía, 2004)
Up to now discussions about multiculturalism have been presented as a progressive revision of the limits of liberalism concerning politics of inclusion and recognition. This paper states that the reception of multiculturalism in Latin America, if doesn't intend to be merely procedural, can be stated in terms of a deconstruction of the concepts of Subject and State. For this purpose, we have adopted the point of view of ethnically differentiated communities (that Deleuze and Guattari have categorized as territorial machines), so that their power relations and their process of subjectivation can be seen as an expression of the infrastate and the suprastate levels, respectively. Even though this difference of perspective is basically put as a dispute between theories, at the end, criteria for a wider debate about the relations between State and capitalism around the conditions of existence of premodern societies are presented.